Direct 3D ultrasound fusion for transesophageal echocardiography. (July 2021) - Mao, Zhehua; Zhao, Liang; Huang, Shoudong; Fan, Yiting; Pui-Wai Lee, Alex
Abstract: Background: Real-time three-dimensional transesophageal echocardiography (3D TEE) has been increasingly used in clinic for fast 3D analysis of cardiac anatomy and function. However, 3D TEE still suffers from the limited field of view (FoV). It is challenging to adopt conventional multi-view fusion methods to 3D TEE images because feature-based registration methods tend to fail in the ultrasound scenario, and conventional intensity-based methods have poor convergence properties and require an iterative coarse-to-fine strategy. Methods: A novel multi-view registration and fusion method is proposed to enlarge the FoV of 3D TEE images efficiently. A direct method is proposed to solve the registration problem in the Lie algebra space. Fast implementation is realized by searching voxels on three orthogonal planes between two volumes. Besides, a weighted-average 3D fusion method is proposed to fuse the aligned images seamlessly. For a sequence of 3D TEE images, they are fused incrementally. Results: Qualitative and quantitative results of in-vivo experiments indicate that the proposed registration algorithm outperforms a state-of-the-art PCA-based registration method in terms of accuracy and efficiency. Image registration and fusion performed on 76 in-vivo 3D TEE volumes from nine patients show apparent enlargement of FoV (enlarged around two times) in the obtained fused images. Conclusions: The proposed methods can fuse 3D TEE images efficiently and accurately so that the whole Region of Interest (ROI) can be seen in a single frame. This research shows good potential to assist clinical diagnosis, preoperative planning, and future intraoperative guidance with 3D TEE. Highlights: 3D Transesophageal Echocardiography imaging is limited by small field of view (FoV). A novel direct method is proposed to enlarge the FoV of the images efficiently. Fast implementation is realized by searching voxels on three orthogonal planes. The proposed registration method outperforms the state-of-the-art PCA-based method. 3D printing of a complete left atrium facilitates preoperative planning.